Agent-based model for forecasting the impact of the population life quality on migration movement in the context of the Russian Federation federal districts. - M. M. Nizamutdinov; Z. A. Davletova (Управленческие науки)
The Russian Federation is characterized by an extremely uneven distribution of the population across the country, which contributes to the asymmetry of economic and socio-demographic development of the regions, a shortage of qualified specialists for the development of the resources of Siberia and the Far East, and an increase in global risks in general.  In this regard, the use of modern management technologies, in particular, multi-agent simulation modeling, to support decision-making on managing migration processes becomes relevant. Since the main incentive for active citizens to change their place of residence is investing in the development of the region and providing the necessary conditions for a comfortable life, the purpose of the study is to develop an agent-based model for forecasting the impact of the population life quality on migration flows between the federal districts of the Russian Federation. One of the tasks solved using the model is to track the direction of migrant movement relative to the Republic of Bashkortostan when changing the controlled parameters. The simulation model was designed using modern CASE tools; UML diagrams and a mnemonic diagram of the decision-making support process for managing the demographic development of the region were built in the course of the work. Scenario experiments were conducted to predict changes in the population size in the study areas. Within the framework of the research, the authors applied the object-oriented methodology of simulation model design, agent-based approach for its implementation, as well as an agent-oriented approach for its implementation and statistical analysis methods when setting up experiments. The toolkit developed as a result of the study can be used by the representatives of executive authorities and government officials to develop a balanced resettlement policy, assess the possibility and conditions for developing regions of the Russian Federation with low population density.